A radiation oncology approach to brain metastases - Wijetunga, N. A.; Yang, T. J. (Frontiers in Neurology, 2020)
Brain metastases are a significant contributor to morbidity and mortality. The incidence of brain metastases is increasing due to increased time for metastasis development in the setting of improved systemic therapy and extracranial disease control and improved detection by magnetic resonance imaging. Radiotherapy is an essential treatment modality for brain metastases in both the definitive and post-surgical adjuvant treatment contexts, and radiation oncologists rely heavily on diagnostic neuroimaging to guide treatment. Insight into the aspects of diagnostic neuroimaging that radiation oncologists rely on for clinical decision-making, radiation treatment planning, and assessment of treatment response or complications, can help guide radiologists when constructing their neuroimaging reports in the context of brain metastases.